FACES E INTERFACES DAS MÚLTIPLAS TELAS: a comunicação nas plataformas audiovisuais digitais - Porto, Aline Farias Martins Oliveira (2013)
Society is digital and lives benefits, challenges and paradigms of this age. Changes are blistering and the time of adaptation to them is shorter each day. Human communication relations with machines are modifying in a deep way, mainly audiovisual screens multiplication that spread through people s life, that are assisted by uncountable Personal Digital Assistants (PDAs) and other ubiquitous displays that converge in a radical way. Technological profusion and sensorial appropriation of contemporaneous instruments are tangible examples of that. With this scenario in a first plan, our research proposes contextualize, describe and analyze new faces and interfaces of communication that materialize in current digital audiovisual platforms, more and more mobile, connected and faster. That way, it undertakes an exploratory study that would mainly worth by specific bibliographic survey and statistical data analysis. The research indicated that the multiple screens, in fact, are changing the dynamics of communication processes, which need to be understood again.